A line in the sand / A Novel - Powers, Kevin (New York : Little, Brown and Company, 2023)
"Since relocating from Iraq to Virginia in 2004 and narrowly surviving an assassination attempt that killed the rest of his family, former translator Arman Bajalan clings to his mundane routine like a lifeline-his daily early morning swim followed by work at the Sea Breeze Motel. But when he finds a dead body on the beach, he is sure that the murder is connected to his past. He is still not safe. Meanwhile, Trevor Graves is on the cusp of becoming a billionaire as the head of Decision Tree International, a corporation which has managed to get high-profile government defense contracts by nefarious means."--
Keywords: Iraq War, 2003-2011 -- Veterans -- Fiction; Journalists -- Fiction; Murder -- Investigation -- Fiction; Translators -- Fiction; Refugees -- Fiction; War crimes -- Fiction; Veterans -- Fiction; Women detectives -- Fiction; Detectives -- Fiction; Virginia -- Fiction; Detective and mystery fiction; Thrillers (Fiction)